Mutual information: a measure of dependency for nonlinear time series - Dionísio, A.; Menezes, R.; Mendes, D. A. (Physica A, 2004)
The main goal of the paper is to show how mutual information can be used as a measure of dependence in financial time series. One major advantage of this approach resides precisely in its ability to account for nonlinear dependencies with no need to specify a theoretical probability distribution or use of a mean-variance model.